Oxidative photo-deposition of chromia: tuning the activity for overall water splitting of the Rh/CrOx co-catalyst system. Issue 33 (10th August 2017) - Menze, J.; Mei, B.; Weide, P.; Muhler, M.
Abstract : By employing an oxidative photodeposition of CrO x the Rh/CrO x co-catalyst system was prepared on Ga2 O3 and Ta2 O5 resulting in up to 25% higher overall water splitting activities. Abstract : Employing an oxidative photodeposition of CrO x the well-known Rh/CrO x co-catalyst system was prepared on different semiconductors. These photocatalysts showed up to 25% higher overall water splitting activities compared with conventionally prepared materials. The enhancement is attributed to a favorable selective deposition of CrO x caused by charge-directed deposition.